Optimalisasi Keuntungan Menggunakan Metode Branch And Bound Pada Produksi Spring Bed - Daryana Dali; Yopi Andry Lesnussa; Venn Yan Ishak Ilwaru (Jurnal Matematika, 2022)
PT Satelit Maluku is a company that produces spring beds with three types, namely 2in1, ordinary spring beds and single beds. Every company established aims to get big profits as well as PT Satelit Maluku. To obtain large profits, companies need to make strategies so that each available material can be allocated optimally and appropriately. The purpose of this research is PT Satelit Maluku can optimize the profit of spring bed production by using the Branch and Bound and QM for Windows V5 methods. From the results of calculations using the Branch and Bound method and QM for windows V5, the optimal profit is Rp. 19,775,000 with a lot of production of spring bed type 2in1 is 0 (not producing), ordinary spring bed is 26 pieces and single bed is 3 pieces.